The Role Of LPS Socialization Strategy Through Deposit Surveys In Increasing Confidence In The Deposits Guarantee Program - Nasution, Suswati; MD , Eska Prima; Wagini, Wagini; Nasution, Siti Wardah Pratidina (Universitas Dehasen Bengkulu, 2025)
This study aims to examine the role of the public outreach strategy implemented by the Indonesia Deposit Insurance Corporation (LPS) through depositor surveys, and its impact on public trust in the deposit insurance program. Although surveys are typically positioned as research instruments, in this context they also serve as tools for public education and information dissemination. This research employs a qualitative descriptive approach using thematic analysis, based on the model proposed by Miles and Huberman (1994), which includes data reduction, data display, and conclusion drawing. The data were obtained from surveys involving 30 depositors with diverse demographic backgrounds and levels of financial literacy. The findings indicate that participation in the survey indirectly enhanced respondents' awareness and understanding of the existence and functions of LPS. Several respondents admitted that they became aware of the deposit insurance program only after taking part in the survey, suggesting that surveys can be an effective outreach tool when designed to be communicative and interactive. In addition, most respondents expressed high levels of trust in financial institutions, including LPS, despite their initially limited understanding of the program. This study concludes that survey-based outreach strategies hold significant potential as non-traditional methods to build public trust in financial institutions. Therefore, surveys should not be viewed merely as data collection tools, but also as strategic communication media within the broader framework of institutional public engagement. LPS is encouraged to further develop survey formats that promote active participation, simultaneous education, and sustainable improvements in public financial literacy.